The Fe(III) complexes with a doubly deprotonated polydentate acylhydrazone: Crystal structure of the first diamagnetic μ-oxo-diiron(III) complex - Bacchi, Alessia; Ivanovic-Burmazovic, Ivana; Pelizzi, Giancarlo; Andjelkovic, K. (Inorganica Chimica Acta, 2001)
The synthesis of two Fe(III) complexes with a doubly deprotonated polydentate of the acylhydrazone class is described. The first complex was obtained by hydrolyzing the previously synthesized high-spin pentagonal-bipyramidal (PBP) [Fe(Hdapsox)Cl] (Hdapsox = 2′,2‴-(2,6-pyridindiyldiethylidene)dioxamohydrazide); the second was obtained by a template synthesis in a base medium starting from iron(III) chloride, 2,6-diacetylpyridine (dap) and semioxamazide (sox) (in a 1:1:2 molar ratio). Hydrolysis, during which the semioxamazide amide group changed into a carboxyl group, resulted in the μ-oxo-diiron(III) complex [Fe(dapoamh)(HO)]O·3HO (Hdapoamh = dioxo-2,6-pyridinediylbis(ethylidyne-1-hydrazinyl-2-ylidene)diacetic acid) with a doubly deprotonated acylhydrazone that retained its PBP geometry. The [Fe(dapsox)Cl]·HO complex obtained in the latter case has a square-pyramidal geometry with an asymmetrically coordinated, but still doubly deprotonated dapsox as a tetradentate. The structure of the [Fe(dapoamh)(HO)]O·3HO complex determined by single-crystal X-ray analysis in this work represents the first μ-oxo-dimer of a PBP geometry with an acyclic polydentate. This is also the first diamagnetic μ-oxo-diiron(III) complex ever obtained; this not only points to the super-exchange interaction over an oxo-oxygen, but also to a significant interaction between the two low-spin Fe(III) ion d-orbitals. Based on the EPR spectra, it has been established that the monomer [Fe(dapsox)Cl]·HO complex is among the rare Fe(III) complexes with an intermediate spin state S = 3/2, and that a temperature decrease causes it to change to a low-spin complex, i.e. it demonstrates a cross-over (S = 3/2 ⇄ S = 1/2). Further characterization has been done by IR and UV - VIS spectroscopy, and also by measuring the magnetic momentum at 293, 195 and 77 K. The results of this work, as well as of the previously synthesized Cu(II), Co(II) and Ni(II) complexes with Hdapsox, Hdapsox and dapsox, have led us to the conclusion that the doubly deprotonated acylhydrazone ligand has a considerably stronger field than its neutral or monoanionic forms. © 2001 Elsevier Science B.V.